Parameter identification of servo-pneumatic position control system utilizing least square estimate (LSE) approach - Nur’iffah, Mohamed Azmi (2009)
This project focused on the parameter identification of Servo-Pneumatic Position Control System (SPPCS) utilizing Least Square Estimate (LSE) approach. The obtained mathematical is analyzed in terms of transient and steady-state response. Presented method is based on the transfer function estimation, these were identified in calculation of the collection of the input and output data by using the LSE method approach. The mathematical model’s parameter is estimated from the calculation. The mathematical model estimation is implemented using the MATLAB’s simulation. The output performance from both MATLAB and Visual Basic (VB) will be compared and if the result is similar and the average error, e is smaller, then the results are accepted. The result obtained is a mathematical model that will be used as parameter identification for SPPCS. In the future, this parameter identification can be used to represent the whole of SPPCS in the MATLAB’s simulation to replace the actual hardware.